Skip to main content

# Weighted endpoint estimates for multilinear commutator of singular integral operators with non-smooth kernels

## Abstract

In this paper, we prove the weighted endpoint estimates for multilinear commutator of singular integral operators with non-smooth kernels.

## 1 Introduction

Let $b∈BMO( R n )$ and T be the Calderón-Zygmund operator, the commutator $[b,T]$ generated by b and T is defined by $[b,T](f)(x)=b(x)T(f)(x)−T(bf)(x)$. A classical result of Coifman et al. (see ) proved that the commutator $[b,T]$ is bounded on $L p ( R n )$ ($1). In [2, 3], the boundedness properties of the commutators for the extreme values of p are obtained. In this paper, we will introduce the multilinear commutator of singular integral operators with non-smooth kernels and prove the weighted boundedness properties of the operator for the extreme cases.

First let us introduce some notations (see ). In this paper, Q will denote a cube of $R n$ with sides parallel to the axes. For a cube Q and a function b, let $b Q = | Q | − 1 ∫ Q b(x)dx$ and $b(Q)= ∫ Q b(x)dx$, the sharp function of b is defined by

$b # (x)= sup Q ∋ x 1 | Q | ∫ Q |b(y)− b Q |dy.$

It is well known that (see )

$b # (x)= sup Q ∋ x inf c ∈ C 1 | Q | ∫ Q |b(y)−c|dy.$

Moreover, for a weight function ω (that is, a non-negative locally integrable function), b is said to belong to $BMO(ω)$ if $b # ∈ L ∞ (ω)$ and define $∥ b ∥ BMO ( ω ) = ∥ b # ∥ L ∞ ( ω )$, if $ω=1$, we denote $BMO(ω)=BMO( R n )$. It is well known that (see )

$∥ b − b 2 k Q ∥ BMO ≤Ck ∥ b ∥ BMO .$

The $A p$ weight is defined by (see )

$A p = { 0 < ω ∈ L loc 1 ( R n ) : sup Q ( 1 | Q | ∫ Q ω ( x ) d x ) ( 1 | Q | ∫ Q ω ( x ) − 1 / ( p − 1 ) d x ) p − 1 < ∞ } , 1 < p < ∞$

and

$A 1 = { 0 < ω ∈ L loc 1 ( R n ) : sup Q ∋ x 1 | Q | ∫ Q ω ( y ) d y ≤ c ω ( x ) , a.e. } .$

Definition 1 A family of operators $D t$, $t>0$, is said to be an ‘approximation to the identity’ if, for every $t>0$, $D t$ can be represented by the kernel $a t (x,y)$ in the following sense:

$D t (f)(x)= ∫ R n a t (x,y)f(y)dy$

for every $f∈ L p ( R n )$ with $p≥1$, and $a t (x,y)$ satisfies

$| a t (x,y)|≤ h t (x,y)=C t − n / 2 s ( | x − y | 2 / t ) ,$

where s is a positive, bounded, and decreasing function satisfying

$lim r → ∞ r n + ϵ s ( r 2 ) =0$

for some $ϵ>0$.

Definition 2 A linear operator T is called the singular integral operators with non-smooth kernels if T is bounded on $L 2 ( R n )$ and associated with a kernel $K(x,y)$ such that

$T(f)(x)= ∫ R n K(x,y)f(y)dy$

for every continuous function f with compact support, and for almost all x not in the support of f.

1. (1)

There exists an ‘approximation to the identity’ ${ B t ,t>0}$ such that $T B t$ has associated kernel $k t (x,y)$ and there exist $c 1 , c 2 >0$ so that

2. (2)

There exists an ‘approximation to the identity’ ${ A t ,t>0}$ such that $A t T$ has associated kernel $K t (x,y)$ which satisfies

and

for some $c 3 , c 4 >0$, $δ>0$.

Given some locally integrable functions $b j$ ($j=1,…,m$). The multilinear operator associated to T is defined by

$T b (f)(x)= ∫ R n [ ∏ j = 1 m ( b j ( x ) − b j ( y ) ) ] K(x,y)f(y)dy.$

Definition 3 Given the ‘approximations to the identity’ ${ A t ,t>0}$ and a weight function ω.

1. (1)

The weighted BMO space associated with ${ A t ,t>0}$ is defined by

$BMO A (ω)= { f ∈ L loc 1 ( R n ) : ∥ f ∥ BMO A ( ω ) < ∞ } ,$

where

$∥ f ∥ BMO A ( ω ) = sup Q 1 ω ( Q ) ∫ Q |f(x)− A t Q (f)(x)|ω(x)dx,$

$t Q =l ( Q ) 2$ and $l(Q)$ denotes the side length of Q.

2. (2)

The weighted central BMO space associated with ${ A t ,t>0}$ is defined by

$CMO A (ω)= { f ∈ L loc 1 ( R n ) : ∥ f ∥ CMO A ( ω ) < ∞ } ,$

where

$∥ f ∥ CMO ( ω ) = sup r > 1 1 ω ( Q ( 0 , r ) ) ∫ Q |f(x)− A t Q f(x)|ω(x)dx,$

and $t Q = r 2$.

Definition 4 Let $1 and ω be a weighted function on $R n$. We shall call $B p (ω)$ the space of those functions f on $R n$, such that

$∥ f ∥ B p ( ω ) = sup r > 1 [ ω ( Q ( 0 , r ) ) ] − 1 / p ∥ f χ Q ( 0 , r ) ∥ L p ( ω ) <∞.$

For $b j ∈BMO( R n )$ ($j=1,…,m$), set $∥ b → ∥ BMO = ∏ j = 1 m ∥ b j ∥ BMO$. Given a positive integer m and $1≤j≤m$, we denote by $C j m$ the family of all finite subsets $σ={σ(1),…,σ(j)}$ of ${1,…,m}$ of j different elements. For $σ∈ C j m$, set $σ c ={1,…,m}∖σ$. For $b → =( b 1 ,…, b m )$ and $σ={σ(1),…,σ(j)}∈ C j m$, set $b → σ =( b σ ( 1 ) ,…, b σ ( j ) )$, $b σ = b σ ( 1 ) ⋯ b σ ( j )$ and $∥ b → σ ∥ BMO = ∥ b σ ( 1 ) ∥ BMO ⋯ ∥ b σ ( j ) ∥ BMO$.

## 2 Theorems and proofs

We begin with some preliminaries lemmas.

Lemma 1 ([5, 7])

Let $ω∈ A 1$, $1, and T be the singular integral operators with non-smooth kernels. Then T is boundedness on $L p (w)$.

Lemma 2 Let $ω∈ A 1$, ${ A t ,t>0}$ be anapproximation to the identityand $b∈BMO( R n )$. Then

1. (a)

for every $f∈ L ∞ ( R n )$, $1≤p<∞$, and any cube Q,

$( 1 | Q | ∫ Q | A t Q ( ( b − b Q ) f ) ( y ) | p d y ) 1 / p ≤C ∥ b ∥ BMO ∥ f ∥ L ∞ ;$
2. (b)

for every $f∈ B p (ω)$, $1≤r, and any cube Q,

$( 1 ω ( Q ) ∫ Q | A t Q ( ( b − b Q ) f ) ( y ) | r ω ( y ) d y ) 1 / r ≤C ∥ b ∥ BMO ∥ f ∥ B p ( ω ) ,$

where $t Q =l ( Q ) 2$ and $l(Q)$ denotes the side length of Q.

Proof (a) Write

$( 1 | Q | ∫ Q | A t Q ( ( b − b Q ) f ) ( y ) | p d y ) 1 / p ≤ ( 1 | Q | ∫ Q ∫ R n h t Q ( x , y ) p | ( b ( y ) − b Q ) f ( y ) | p d y d x ) 1 / p ≤ ( 1 | Q | ∫ Q ∫ 2 Q h t Q ( x , y ) p | ( b ( y ) − b Q ) f ( y ) | p d y d x ) 1 / p + ( ∑ k = 1 ∞ 1 | Q | ∫ Q ∫ 2 k + 1 Q ∖ 2 k Q h t Q ( x , y ) p | ( b ( y ) − b Q ) f ( y ) | p d y d x ) 1 / p = I 1 + I 2 .$

We have, by Hölder’s inequality,

$I 1 ≤ ( C | Q | | 2 Q | ∫ Q ∫ 2 Q | ( b ( y ) − b Q ) f ( y ) | p d y d x ) 1 / p ≤ C ∥ f ∥ L ∞ ( 1 | 2 Q | ∫ 2 Q | b ( y ) − b Q | p d y ) 1 / p ≤ C ∥ b ∥ BMO ∥ f ∥ L ∞ .$

For $I 2$, for $x∈Q$ and $y∈ 2 k + 1 Q∖ 2 k Q$, we have $|x−y|≥ 2 k − 1 t Q$ and $h t Q (x,y)≤C s ( 2 2 ( k − 1 ) ) | Q |$. Thus

$I 2 ≤ C ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q | ( b ( y ) − b Q ) f ( y ) | p d y ) 1 / p ≤ C ∥ f ∥ L ∞ ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q | b ( y ) − b 2 k + 1 Q | p d y ) 1 / p + C ∥ f ∥ L ∞ ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) | b Q − b 2 k + 1 Q | ≤ C ∥ f ∥ L ∞ ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( k + 1 ) ∥ b ∥ BMO ≤ C ∥ b ∥ BMO ∥ f ∥ L ∞ ,$

where the last inequality follows from

$∑ k = 2 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) (k+1)≤C ∑ k = 2 ∞ k 2 − ( k − 1 ) ϵ <∞$

for some $ϵ>0$.

1. (b)

Write

$( 1 ω ( Q ) ∫ Q | A t Q ( ( b − b Q ) f ) ( y ) | r ω ( y ) d y ) 1 / r ≤ ( 1 ω ( Q ) ∫ Q ∫ R n h t Q ( x , y ) r | ( b ( y ) − b Q ) f ( y ) | r ω ( y ) d y d x ) 1 / r ≤ ( 1 ω ( Q ) ∫ Q ∫ 2 Q h t Q ( x , y ) p | ( b ( y ) − b Q ) f ( y ) | r ω ( y ) d y d x ) 1 / r + ( ∑ k = 1 ∞ 1 ω ( Q ) ∫ Q ∫ 2 k + 1 Q ∖ 2 k Q h t Q ( x , y ) r | ( b ( y ) − b Q ) f ( y ) | r ω ( y ) d y d x ) 1 / r = I + II .$

For I, since $ω∈ A 1$, ω satisfies the reverse of Hölder’s inequality

$( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / q ≤ C | Q | ∫ Q ω(x)dx$

for some $1, and $ω ( Q 2 ) | Q 2 | | Q 1 | ω ( Q 1 ) ≤C$ for all cubes $Q 1$, $Q 2$ with $Q 1 ⊂ Q 2$, $ω∈ A p / r u$ for $1 with $u ′ v=q$ and $p>ru$ (see ). We have, by Hölder’s inequality,

$I ≤ ( C ω ( Q ) | Q | ∫ Q ∫ 2 Q | ( b ( y ) − b Q ) f ( y ) | r ω ( y ) d y d x ) 1 / r I ≤ C ( 1 ω ( Q ) ∫ 2 Q | ( b ( y ) − b Q ) f ( y ) | r ω ( y ) d y ) 1 / r I ≤ C [ | 2 Q | ω ( Q ) ( 1 | 2 Q | ∫ 2 Q | b ( y ) − b Q | r u ′ ω ( y ) u ′ d y ) 1 / u ′ ( 1 | 2 Q | ∫ 2 Q | f ( y ) | r u d y ) 1 / u ] 1 / r I ≤ C ( | 2 Q | ω ( Q ) ) 1 / r ( 1 | 2 Q | ∫ 2 Q | b ( y ) − b Q | r u ′ v ′ d y ) 1 / r u ′ v ′ ( 1 | 2 Q | ∫ 2 Q ω ( y ) u ′ v d y ) 1 / r u ′ v I ≤ × ( 1 | 2 Q | ∫ 2 Q | f ( y ) | r u d y ) 1 / r u I ≤ C ∥ b ∥ BMO ( | 2 Q | ω ( 2 Q ) ) 1 / r ( ω ( 2 Q ) | 2 Q | ) 1 / r ( 1 | 2 Q | ∫ 2 Q | f ( y ) | r u ω ( y ) r u p ω ( y ) − r u p d y ) 1 / r u I ≤ C ∥ b ∥ BMO ( 1 | 2 Q | ∫ 2 Q ( | f ( y ) | r u ω ( y ) r u p ) p r u d y ) 1 / p ( 1 | 2 Q | ∫ 2 Q ω ( y ) − r u p p p − r u d y ) ( p − r u ) / p r u I ≤ C ∥ b ∥ BMO ( 1 | 2 Q | ) 1 / p ∥ f χ 2 Q ∥ L p ( ω ) ( 1 | 2 Q | ∫ 2 Q ω ( y ) d y ) − 1 / p I ≤ × [ ( 1 | 2 Q | ∫ 2 Q ω ( y ) d y ) ( 1 | 2 Q | ∫ 2 Q ω ( y ) − 1 p r u − 1 d y ) p r u − 1 ] 1 / p I ≤ C ∥ b ∥ BMO ω ( 2 Q ) − 1 / p ∥ f χ 2 Q ∥ L p ( ω ) I ≤ C ∥ b ∥ BMO ∥ f ∥ B p ( ω ) ; II ≤ C ( | Q | ω ( Q ) ) 1 / r ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q | ( b ( y ) − b Q ) f ( y ) | r ω ( y ) d y ) 1 / r II ≤ C ( | Q | ω ( Q ) ) 1 / r ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q | b ( y ) − b 2 k + 1 Q | r u ′ ω ( y ) u ′ d y ) 1 / r u ′ II ≤ × ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q | f ( y ) | r u d y ) 1 / r u II ≤ C ( | Q | ω ( Q ) ) 1 / r ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q | b ( y ) − b 2 k + 1 Q | r u ′ v ′ d y ) 1 / r u ′ v ′ II ≤ × ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q ω ( y ) u ′ v d y ) 1 / r u ′ v ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q f ( y ) r u d y ) 1 / r u II ≤ C ∥ b ∥ BMO ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( k + 1 ) ( | Q | ω ( Q ) ⋅ ω ( 2 k + 1 Q ) | 2 k + 1 Q | ) 1 / r II ≤ × ( 1 | 2 k + 1 Q | ∫ 2 k + 1 Q f ( y ) r u d y ) 1 / r u II ≤ C ∑ k = 1 ∞ 2 ( k − 1 ) n s ( 2 2 ( k − 1 ) ) ( k + 1 ) ∥ b ∥ BMO ω ( 2 k + 1 Q ) − 1 / p ∥ f χ 2 k + 1 Q ∥ L p ( ω ) II ≤ C ∥ b ∥ BMO ∥ f ∥ B p ( w ) .$

This completes the proof. □

Theorem 1 Let T be the singular integral operators with non-smooth kernels, $ω∈ A 1$ and $b → =( b 1 ,…, b m )$ with $b j ∈BMO( R n )$ for $1≤j≤m$. Then $T b$ is bounded from $L ∞ (ω)$ to $BMO A (ω)$.

Proof It suffices to prove, for $f∈ C 0 ∞ ( R n )$, the following inequality holds:

$1 ω ( Q ) ∫ Q | T b (f)(x)− A t Q T b (f)(x)|ω(x)dx≤C ∥ f ∥ L ∞ ( ω ) .$

We fix a cube $Q=Q( x 0 ,d)$. We decompose f into $f= f 1 + f 2$ with $f 1 =f χ Q$, $f 2 =f χ ( R n ∖ Q )$.

When $m=1$, set $( b 1 ) Q = | Q | − 1 ∫ Q b 1 (y)dy$, we have

$T b 1 ( f ) ( x ) = ∫ R n [ ( b 1 ( x ) − ( b 1 ) Q ) − ( b 1 ( y ) − ( b 1 ) Q ) ] K ( x , y ) f ( y ) d y = ( b 1 ( x ) − ( b 1 ) Q ) ∫ R n K ( x , y ) f ( y ) d y − ∫ R n ( b 1 ( y ) − ( b 1 ) Q ) K ( x , y ) f ( y ) d y$

and

$A t Q T b 1 (f)(x)= ( b 1 ( x ) − ( b 1 ) Q ) ∫ R n K t (x,y)f(y)dy− ∫ R n ( b 1 ( y ) − ( b 1 ) Q ) K t (x,y)f(y)dy.$

Then

$| T b 1 ( f ) ( x ) − A t Q T b 1 ( f ) ( x ) | ≤ | ( b 1 ( x ) − ( b 1 ) Q ) ∫ R n K ( x , y ) f ( y ) d y | + | ∫ R n ( b 1 ( y ) − ( b 1 ) Q ) K ( x , y ) f 1 ( y ) d y | + | ( b 1 ( x ) − ( b 1 ) Q ) ∫ R n K t ( x , y ) f ( y ) d y | + | ∫ R n ( b 1 ( y ) − ( b 1 ) Q ) K t ( x , y ) f 1 ( y ) d y | + | ∫ R n ( b 1 ( y ) − ( b 1 ) Q ) ( K ( x , y ) − K t ( x , y ) ) f 2 ( y ) d y | = I 1 ( x ) + I 2 ( x ) + I 3 ( x ) + I 4 ( x ) + I 5 ( x ) .$

For $I 1 (x)$, let $1/p+1/ p ′ =1$, $1/q+1/ q ′ =1$, by the reverse of Hölder’s inequality with $1, Lemma 1, and Hölder’s inequality, we have

$1 ω ( Q ) ∫ Q | I 1 ( x ) | ω ( x ) d x ≤ C ω ( Q ) ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p ′ ω ( x ) d x ) 1 / p ′ ( ∫ R n | T ( f ) ( x ) | p ω ( x ) χ Q ( x ) d x ) 1 / p ≤ C ω ( Q ) ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p ′ ω ( x ) d x ) 1 / p ′ ( ∫ R n | f ( x ) | p ω ( x ) χ Q ( x ) d x ) 1 / p ≤ C ω ( Q ) ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p ′ ω ( x ) d x ) 1 / p ′ ∥ f ∥ L ∞ ( ω ) ( ∫ Q ω ( x ) d x ) 1 / p ≤ C ω ( Q ) [ ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p ′ q ′ d x ) 1 / q ′ ( ∫ Q ω ( x ) q d x ) 1 / q ] 1 / p ′ ∥ f ∥ L ∞ ( ω ) ω ( Q ) 1 / p ≤ C ω ( Q ) 1 / p − 1 | Q | 1 / p ′ ∥ b 1 ∥ BMO ( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / p ′ q ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

For $I 2 (x)$, taking $p>1$, by Hölder’s inequality, we have

$1 ω ( Q ) ∫ Q | I 2 ( x ) | ω ( x ) d x ≤ ( 1 ω ( Q ) ∫ R n | T ( ( b 1 − ( b 1 ) Q ) f 1 ) ( x ) | p ω ( x ) χ Q ( x ) d x ) 1 / p ≤ C ω ( Q ) − 1 / p ( ∫ R n | ( b 1 ( x ) − ( b 1 ) Q ) f 1 ( x ) | p ω ( x ) χ Q ( x ) d x ) 1 / p ≤ C ω ( Q ) − 1 / p [ ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p q ′ d x ) 1 / q ′ ( ∫ Q | f ( x ) | p q ω ( x ) q d x ) 1 / q ] 1 / p ≤ C ω ( Q ) − 1 / p ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p q ′ d x ) 1 / p q ′ ( ∫ Q | f ( x ) | p q ω ( x ) q d x ) 1 / p q ≤ C ω ( Q ) − 1 / p ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p q ′ d x ) 1 / p q ′ ( ∫ Q ω ( x ) q d x ) 1 / p q ∥ f ∥ L ∞ ( ω ) ≤ C ω ( Q ) − 1 / p | Q | 1 / p q ′ ∥ b 1 ∥ BMO | Q | 1 / p q ( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / p q ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b 1 ∥ BMO ( | Q | ω ( Q ) ) 1 / p ( 1 | Q | ∫ Q ω ( x ) d x ) 1 / p ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

For $I 3 (x)$ and $I 4 (x)$, we get, for $1< p 1 , p 2 <∞$ with $1/ p 1 +1/ p 2 +1/q=1$,

$1 ω ( Q ) ∫ Q | I 3 ( x ) | ω ( x ) d x ≤ C ω ( Q ) ∫ Q | b 1 ( x ) − ( b 1 ) Q | | A t Q ( f ) ( x ) | ω ( x ) d x ≤ C | Q | ω ( Q ) ( 1 | Q | ∫ Q | b 1 ( x ) − ( b 1 ) Q | p 1 d x ) 1 / p 1 × ( 1 | Q | ∫ Q | A t Q ( f ) ( x ) | p 2 d x ) 1 / p 2 ( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / q ≤ C | Q | ω ( Q ) ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) ω ( Q ) | Q | ≤ C ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) , 1 ω ( Q ) ∫ Q | I 4 ( x ) | ω ( x ) d x ≤ 1 ω ( Q ) ∫ R n | A t Q ( ( b 1 − ( b 1 ) Q ) f 1 ) ( x ) | ω ( x ) d x ≤ C | Q | ω ( Q ) ( 1 | Q | ∫ Q | A t Q ( ( b 1 − ( b 1 ) Q ) f 1 ) ( x ) | q ′ d x ) 1 / q ′ ( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / q ≤ C | Q | ω ( Q ) ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) ω ( Q ) | Q | ≤ C ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

For $I 5 (x)$, we have

$I 5 ( x ) = | ∫ R n ( b 1 ( y ) − ( b 1 ) Q ) ( K ( x , y ) − K t ( x , y ) ) f 2 ( y ) d y | ≤ C ∑ k = 0 ∞ ∫ 2 k + 1 Q ∖ 2 k Q | b 1 ( y ) − ( b 1 ) Q | | f ( y ) | d δ | x 0 − y | n + δ d y ≤ C ∑ k = 1 ∞ d δ ( 2 k − 1 d ) n + δ | 2 k Q | ( 1 | 2 k Q | ∫ 2 k Q | f ( y ) | p d y ) 1 / p × ( 1 | 2 k Q | ∫ 2 k Q | b 1 ( y ) − ( b 1 ) Q | p ′ d y ) 1 / p ′ ≤ C ∑ k = 1 ∞ k m 2 − k δ ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) ,$

so

$1 ω ( Q ) ∫ Q | I 5 (x)|ω(x)dx≤C ∥ b 1 ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

When $m>1$, set $b → Q =( ( b 1 ) Q ,…, ( b m ) Q )∈ R n$, where $( b j ) Q = | Q | − 1 ∫ Q b j (y)dy$, $1≤j≤m$, we have

$T b ( f ) ( x ) = ∏ j = 1 m ( b j ( x ) − ( b j ) Q ) ∫ R n K ( x , y ) f ( y ) d y + ∑ j = 1 m − 1 ∑ σ ∈ C j m ( − 1 ) m − j ( b ( x ) − ( b ) Q ) σ ∫ R n ( b ( y ) − ( b ) Q ) σ c K ( x , y ) f ( y ) d y + ( − 1 ) m ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) K ( x , y ) f ( y ) d y$

and

$A t Q T b ( f ) ( x ) = ∏ j = 1 m ( b j ( x ) − ( b j ) Q ) ∫ R n K t ( x , y ) f ( y ) d y + ∑ j = 1 m − 1 ∑ σ ∈ C j m ( − 1 ) m − j ( b ( x ) − ( b ) Q ) σ ∫ R n ( b ( y ) − ( b ) Q ) σ c K t ( x , y ) f ( y ) d y + ( − 1 ) m ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) K t ( x , y ) f ( y ) d y ,$

then

$| T b ( f ) ( x ) − A t Q T b ( f ) ( x ) | ≤ | ∏ j = 1 m ( b j ( x ) − ( b j ) Q ) ∫ R n K ( x , y ) f ( y ) d y | + | ∑ j = 1 m − 1 ∑ σ ∈ C j m ( b ( x ) − ( b ) Q ) σ ∫ R n ( b ( y ) − ( b ) Q ) σ c K ( x , y ) f ( y ) d y | + | ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) K ( x , y ) f 1 ( y ) d y | + | ∏ j = 1 m ( b j ( x ) − ( b j ) Q ) ∫ R n K t ( x , y ) f ( y ) d y | + | ∑ j = 1 m − 1 ∑ σ ∈ C j m ( b ( x ) − ( b ) Q ) σ ∫ R n ( b ( y ) − ( b ) Q ) σ c K t ( x , y ) f ( y ) d y | + | ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) K t ( x , y ) f 1 ( y ) d y | + | ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) ( K ( x , y ) − K t ( x , y ) ) f 2 ( y ) d y | = J 1 ( x ) + J 2 ( x ) + J 3 ( x ) + J 4 ( x ) + J 5 ( x ) + J 6 ( x ) + J 7 ( x ) .$

For $J 1 (x)$, same as $m=1$, for some $1, let $1/ q 1 +1/ q 2 +⋯+1/ q m +1/q=1$, $1/p+1/ p ′ =1$, by Hölder’s inequality, and the reverse of Hölder’s inequality, we get

$1 ω ( Q ) ∫ Q | J 1 ( x ) | ω ( x ) d x ≤ C ω ( Q ) ( ∫ Q | ( b 1 ( x ) − ( b 1 ) Q ) ⋯ ( b m ( x ) − ( b m ) Q ) | p ′ ω ( x ) d x ) 1 / p ′ × ( ∫ Q | T ( f ) ( x ) | p ω ( x ) d x ) 1 / p ≤ C ω ( Q ) ( ∫ Q | b 1 ( x ) − ( b 1 ) Q | p ′ ⋯ | b m ( x ) − ( b m ) Q | p ′ ω ( x ) d x ) 1 / p ′ × ∥ f ∥ L ∞ ( ω ) ( ∫ Q ω ( x ) d x ) 1 / p ≤ C ω ( Q ) ∥ f ∥ L ∞ ( ω ) ω ( Q ) 1 / p ∏ j = 1 m [ ( ∫ Q | b j ( x ) − ( b j ) Q | p ′ q j d x ) 1 / q j ( ∫ Q ω ( x ) q d x ) 1 / q ] 1 / p ′ ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) ω ( Q ) 1 / p ′ + 1 / p − 1 | Q | 1 / p ′ ( 1 / q 1 + ⋯ + 1 / q m + 1 / q − 1 ) ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

For $J 2 (x)$, by Hölder’s inequality and the reverse of Hölder’s inequality, we have

$1 ω ( Q ) ∫ Q | J 2 ( x ) | ω ( x ) d x ≤ ∑ j = 1 m − 1 ∑ σ ∈ C j m C ω ( Q ) ( ∫ Q | ( b ( x ) − b Q ) σ | p ′ ω ( x ) d x ) 1 / p ′ × ( ∫ Q | T ( ( b − b Q ) σ c f ) ( x ) | p ω ( x ) d x ) 1 / p ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ( 1 ω ( Q ) ∫ Q | ( b ( x ) − b Q ) σ | p ′ ω ( x ) d x ) 1 / p ′ × ( 1 ω ( Q ) ∫ Q | T ( ( b − b Q ) σ c f ) ( x ) | p ω ( x ) d x ) 1 / p ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ω ( Q ) − 1 / p ′ [ ( ∫ Q | ( b ( x ) − b Q ) σ | p ′ q ′ d x ) 1 / q ′ ( ∫ Q ω ( x ) q d x ) 1 / q ] 1 / p ′ × ω ( Q ) − 1 / p ( ∫ R n | ( b ( x ) − b Q ) σ c f ( x ) | p ω ( x ) χ Q ( x ) d x ) 1 / p ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ω ( Q ) − 1 / p ′ | Q | 1 / p ′ q ′ + 1 / p ′ q − 1 / p ′ ω ( Q ) 1 / p ′ ∥ b → σ ∥ BMO × ω ( Q ) − 1 / p ( ∫ Q | ( b ( x ) − b Q ) σ c | p q ′ d x ) 1 / p q ′ ( ∫ Q | f ( x ) | p q ω q ( x ) d x ) 1 / p q ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ∥ b → σ ∥ BMO ∥ b → σ c ∥ BMO ( | Q | ω ( Q ) ) 1 / p × ( 1 | Q | ∫ Q ω ( x ) d x ) 1 / p ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

For $J 3 (x)$, taking $p>1$, by the $L p (ω)$-boundedness of T, we have

$1 ω ( Q ) ∫ Q | J 3 ( x ) | ω ( x ) d x ≤ ( 1 ω ( Q ) ∫ R n | T ( ( b 1 − ( b 1 ) Q ) ⋯ ( b m − ( b m ) Q ) f 1 ) ( x ) | p ω ( x ) d x ) 1 / p ≤ C ω ( Q ) − 1 / p ( ∫ R n | ( b 1 ( x ) − ( b 1 ) Q ) ⋯ ( b m ( x ) − ( b m ) Q ) f 1 ( x ) | p ω ( x ) d x ) 1 / p ≤ C ω ( Q ) − 1 / p | Q | 1 / p q ′ ∥ b → ∥ BMO | Q | 1 / p q ( 1 | Q | ∫ Q ω q d x ) 1 / p q ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b → ∥ BMO ( | Q | ω ( Q ) ) 1 / p ( ω ( Q ) | Q | ) 1 / p ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

For $J 4 (x)$, $J 5 (x)$, and $J 6 (x)$, choose $1, $j=1,…,m$, such that $1/p+1/ q 1 +⋯+1/ q m +1/q$, by Lemma 2 and similar to the proofs of $J 1 (x)$, $J 2 (x)$, and $J 3 (x)$, we get

$1 ω ( Q ) ∫ Q | J 4 ( x ) | ω ( x ) d x ≤ C | Q | ω ( Q ) ∏ j = 1 m ( 1 | Q | ∫ Q | ( b j ( x ) − ( b j ) Q ) | q j d x ) 1 / q j × ( 1 | Q | ∫ Q | A t Q ( f ) ( x ) | p d x ) 1 / p ( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / q ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) , 1 ω ( Q ) ∫ Q | J 5 ( x ) | ω ( x ) d x ≤ C | Q | ω ( Q ) ∑ j = 1 m − 1 ∑ σ ∈ C j m ( 1 | Q | ∫ Q | ( b ( x ) − b Q ) σ | q ′ d x ) 1 / q ′ × ( 1 | Q | ∫ Q | A t Q ( ( b − b Q ) σ c f ) ( x ) | p d x ) 1 / p ( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / q ≤ C | Q | ω ( Q ) ∑ j = 1 m − 1 ∑ σ ∈ C j m ∥ b → σ ∥ BMO ∥ b → σ c ∥ BMO ∥ f ∥ L ∞ ( ω ) ω ( Q ) | Q | ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) , 1 ω ( Q ) ∫ Q | J 6 ( x ) | ω ( x ) d x ≤ C | Q | ω ( Q ) ( 1 | Q | ∫ Q | A t Q ( ( b 1 − ( b 1 ) Q ) ⋯ ( b m − ( b m ) Q ) f 1 ) ( x ) | q ′ d x ) 1 / q ′ × ( 1 | Q | ∫ Q ω ( x ) q d x ) 1 / q ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

For $J 7 (x)$, note that $|x−y|≥d= t 1 / 2$, taking $1< q j <∞$, $j=1,…,m$ such that $1/ q 1 +⋯+1/ q m +1/r=1$, then

$J 7 ( x ) ≤ C ∑ k = 0 ∞ ∫ 2 k + 1 Q ∖ 2 k Q ∏ j = 1 m | ( b j ( y ) − ( b j ) Q ) | | f ( y ) | d δ | x 0 − y | n + δ d y ≤ C ∑ k = 1 ∞ d δ ( 2 k − 1 d ) n + δ | 2 k Q | ( 1 | 2 k Q | ∫ 2 k Q | f ( y ) | r d y ) 1 / r × ∏ j = 1 m ( 1 | 2 k Q | ∫ 2 k Q | b j ( y ) − ( b j ) Q | q j d y ) 1 / q j ≤ C ∑ k = 1 ∞ 2 − k δ ∥ f ∥ L ∞ ( ω ) ∏ j = 1 m ( 1 | 2 k Q | ∫ 2 k Q | b j ( y ) − ( b j ) Q | q j d y ) 1 / q j ≤ C ∑ k = 1 ∞ k m 2 − k δ ∏ j = 1 m ∥ b j ∥ BMO ∥ f ∥ L ∞ ( ω ) ≤ C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) ,$

so

$1 ω ( Q ) ∫ Q | J 7 (x)|ω(x)dx≤C ∥ b → ∥ BMO ∥ f ∥ L ∞ ( ω ) .$

This completes the proof of Theorem 1. □

Theorem 2 Let $1, $ω∈ A 1$ and $b → =( b 1 ,…, b m )$ with $b j ∈BMO( R n )$ for $1≤j≤m$. Then $T b$ is bounded from $B p (ω)$ to $CMO A (ω)$.

Proof It suffices to prove for $f∈ C 0 ∞ ( R n )$, the following inequality holds:

$1 ω ( Q ) ∫ Q | T b (f)(x)− A t Q T b (f)(x)|ω(x)dx≤C ∥ f ∥ B p ( ω )$

for any cube $Q=Q(0,d)$ with $d>1$. Fix a cube $Q=Q(0,d)$ with $d>1$. Set $f 1 =f χ Q$, $f 2 =f χ ( R n ∖ Q )$ and $b → Q =( ( b 1 ) Q ,…, ( b m ) Q )∈ R n$, where $( b j ) Q = | Q | − 1 ∫ Q | b j (y)|dy$, $1≤j≤m$, we have

$| T b ( f ) ( x ) − A t Q T b ( f ) ( x ) | ≤ | ∏ j = 1 m ( b j ( x ) − ( b j ) Q ) ∫ R n K ( x , y ) f ( y ) d y | + | ∑ j = 1 m − 1 ∑ σ ∈ C j m ( b ( x ) − ( b ) Q ) σ ∫ R n ( b ( y ) − ( b ) Q ) σ c K ( x , y ) f ( y ) d y | + | ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) K ( x , y ) f 1 ( y ) d y | + | ∏ j = 1 m ( b j ( x ) − ( b j ) Q ) ∫ R n K t ( x , y ) f ( y ) d y | + | ∑ j = 1 m − 1 ∑ σ ∈ C j m ( b ( x ) − ( b ) Q ) σ ∫ R n ( b ( y ) − ( b ) Q ) σ c K t ( x , y ) f ( y ) d y | + | ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) K t ( x , y ) f 1 ( y ) d y | + | ∫ R n ∏ j = 1 m ( b j ( y ) − ( b j ) Q ) ( K ( x , y ) − K t ( x , y ) ) f 2 ( y ) d y | = L 1 ( x ) + L 2 ( x ) + L 3 ( x ) + L 4 ( x ) + L 5 ( x ) + L 6 ( x ) + L 7 ( x ) .$

For $L 1 (x)$, we have

$1 ω ( Q ) ∫ Q | L 1 ( x ) | ω ( x ) d x ≤ C ω ( Q ) ( ∫ Q | ( b 1 ( x ) − ( b 1 ) Q ) ⋯ ( b m ( x ) − ( b m ) Q ) | p ′ ω ( x ) d x ) 1 / p ′ × ( ∫ Q | T ( f ) ( x ) | p ω ( x ) d x ) 1 / p ≤ C ω ( Q ) [ ( ∫ Q | ( b 1 ( x ) − ( b 1 ) Q ) ⋯ ( b m ( x ) − ( b m ) Q ) | p ′ q ′ d x ) 1 / q ′ ( ∫ Q ω ( x ) q d x ) 1 / q ] 1 / p ′ × ( ∫ Q | f ( x ) | p ω ( x ) d x ) 1 / p ≤ C ω ( Q ) | Q | 1 / p ′ q ′ ∥ b → ∥ BMO | Q | 1 / p ′ q ( ω ( Q ) | Q | ) 1 / p ′ ∥ f χ Q ∥ L p ( ω ) ≤ C ∥ b → ∥ BMO ω ( Q ) − 1 / p ∥ f χ Q ∥ L p ( ω ) ≤ C ∥ b → ∥ BMO ∥ f ∥ B p ( ω ) .$

For $L 2 (x)$, taking $1, and $1/s+1/ s ′ =1$, we have

$1 ω ( Q ) ∫ Q | L 2 ( x ) | ω ( x ) d x ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ( 1 ω ( Q ) ∫ Q | ( b ( x ) − b Q ) σ | s ′ ω ( x ) d x ) 1 / s ′ × ( 1 ω ( Q ) ∫ Q | T ( ( b − b Q ) σ c f ) ( x ) | s ω ( x ) d x ) 1 / s ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ω ( Q ) − 1 / s ′ [ ( ∫ Q | ( b ( x ) − b Q ) σ | s ′ q ′ d x ) 1 / q ′ ( ∫ Q ω q d x ) 1 / q ] 1 / s ′ × ω ( Q ) − 1 / s ( ∫ Q | ( b ( x ) − b Q ) σ c f ( x ) | s ω ( x ) d x ) 1 / s ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ω ( Q ) − 1 / s ′ | Q | 1 / s ′ q ′ + 1 / s ′ q − 1 / s ′ ω ( Q ) 1 / s ′ ∥ b → σ ∥ BMO × ω ( Q ) − 1 / s | Q | 1 / r s ∥ b → σ c ∥ BMO ( ∫ Q | f ( x ) | p ω ( x ) d x ) 1 / p ( ∫ Q ω ( x ) q d x ) ( p − s ) / p q s ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ∥ b → σ ∥ BMO ∥ b → σ c ∥ BMO ω ( Q ) − 1 / p ∥ f χ Q ∥ L p ( ω ) ≤ C ∥ b → ∥ BMO ∥ f ∥ B p ( ω ) .$

For $L 3 (x)$, we have

$1 ω ( Q ) ∫ Q | L 3 ( x ) | ω ( x ) d x ≤ C ( 1 ω ( Q ) ∫ R n | T ( ( b 1 − ( b 1 ) Q ) ⋯ ( b m − ( b m ) Q ) f 1 ) ( x ) | s ω ( x ) d x ) 1 / s ≤ C ω ( Q ) − 1 / s ( ∫ Q | ( b 1 ( x ) − ( b 1 ) Q ) ⋯ ( b m ( x ) − ( b m ) Q ) f ( x ) | s ω ( x ) d x ) 1 / s ≤ C ω ( Q ) − 1 / p ∥ b → ∥ BMO ∥ f χ Q ∥ L p ( ω ) ≤ C ∥ b → ∥ BMO ∥ f ∥ B p ( ω ) .$

For $L 4 (x)$, $L 5 (x)$, and $L 6 (x)$, by Lemma 2, we have

$1 ω ( Q ) ∫ Q | L 4 ( x ) | ω ( x ) d x ≤ C ( 1 ω ( Q ) ∫ Q | ( b 1 ( x ) − ( b 1 ) Q ) ⋯ ( b m ( x ) − ( b m ) Q ) | s ′ ω ( x ) d x ) 1 / s ′ × ( 1 ω ( Q ) ∫ Q | A t Q ( f ) ( x ) | s ω ( x ) d x ) 1 / s ≤ C ( 1 ω ( Q ) ) 1 / s ′ [ ( ∫ Q | ( b 1 ( x ) − ( b 1 ) Q ) ⋯ ( b m ( x ) − ( b m ) Q ) | s ′ q ′ d x ) 1 / q ′ × ( ∫ Q ω ( x ) q d x ) 1 / q ] 1 / s ′ ∥ f ∥ B p ( w ) ≤ C ( 1 ω ( Q ) ) 1 / s ′ | Q | 1 / s ′ q ′ ∥ b → ∥ BMO | Q | 1 / s ′ q ( ω ( Q ) | Q | ) 1 / s ′ ∥ f ∥ B p ( w ) ≤ C ∥ b → ∥ BMO ∥ f ∥ B p ( ω ) ; 1 ω ( Q ) ∫ Q | L 5 ( x ) | ω ( x ) d x ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ( 1 ω ( Q ) ∫ Q | ( b ( x ) − b Q ) σ | s ′ ω ( x ) d x ) 1 / s ′ × ( 1 ω ( Q ) ∫ Q | A t Q ( ( b − b Q ) σ c f ) ( x ) | s ω ( x ) d x ) 1 / s ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ω ( Q ) − 1 / s ′ [ ( ∫ Q | ( b ( x ) − b Q ) σ | s ′ q ′ d x ) 1 / q ′ ( ∫ Q ω q d x ) 1 / q ] 1 / s ′ × ∥ b → σ c ∥ BMO ∥ f ∥ B p ( ω ) ≤ C ∑ j = 1 m − 1 ∑ σ ∈ C j m ω ( Q ) − 1 / s ′ | Q | 1 / s ′ q ′ + 1 / s ′ q − 1 / s ′ ω ( Q ) 1 / s ′ ∥ b → σ ∥ BMO ∥ b → σ c ∥ BMO ∥ f ∥ B p ( ω ) ≤ C ∥ b → σ ∥ BMO ∥ f ∥ B p ( ω ) ; 1 ω ( Q ) ∫ Q | L 6 ( x ) | ω ( x ) d x ≤ ( 1 ω ( Q ) ∫ R n | A t Q ( ( b 1 − ( b 1 ) Q ) ⋯ ( b m − ( b m ) Q ) f 1 ) ( x ) | s ω ( x ) d x ) 1 / s ≤ C ∥ b → ∥ BMO ∥ f ∥ B p ( ω ) .$

For $L 7 (x)$, note that $|x−y|≥d= t 1 / 2$, taking $1, then

$L 7 ( x ) ≤ C ∫ Q c ∏ j = 1 m | b j ( y ) − ( b j ) Q | | f ( y ) | d δ | x 0 − y | n + δ d y ≤ C ∑ k = 0 ∞ ∫ 2 k + 1 Q ∖ 2 k Q ∏ j = 1 m | b j ( y ) − ( b j ) Q | | f ( y ) | d δ | x 0 − y | n + δ d y ≤ C ∑ k = 1 ∞ d δ ( 2 k − 1 d ) n + δ | 2 k Q | ( 1 | 2 k Q | ∫ 2 k Q | f ( y ) | u d y ) 1 / u × ( 1 | 2 k Q | ∫ 2 k Q ∏ j = 1 m | b j ( y ) − ( b j ) Q | u ′ d y ) 1 / u ′ ≤ C ∥ b → ∥ BMO ∑ k = 1 ∞ k m 2 − k δ ( 1 | 2 k Q | ) 1 / u × [ ( ∫ 2 k Q | f ( y ) | p ω ( y ) d y ) u p ( ∫ 2 k Q ω ( y ) − u p − u d y ) p − u p ] 1 / u ≤ C ∥ b → ∥ BMO ∑ k = 1 ∞ k m 2 − k δ ( 1 | 2 k Q | ) 1 / u ∥ f χ 2 k Q ∥ L p ( ω ) ( ω ( 2 k Q ) | 2 k Q | ) − 1 / p | 2 k Q | ( p u − 1 ) 1 p × [ ( 1 | 2 k Q | ∫ 2 k Q ω ( y ) d y ) ( 1$